FEASIBILITY STUDY FOR ANTISEPTIC GEL FORMULATIONS INCORPORATING THE ESSENTIAL OILS CYMBOPOGON CITRATUS (DC.) STAPF. AND CARYOPHYLLUS AROMATICUS L. - Layane Lenardon Vinciguerra; Caroline Rohr; Graziela Heberlé (Drug Analytical Research, 2018)
Recent years have seen an increase in the search by the pharmaceutical industry for products and active ingredients of natural origin. Additionally, there is a need for the creation of new market products such as antiseptics, used to prevent or reduce the risk of infection by inhibiting the proliferation of microorganisms. The objective of this study was to produce two antiseptic gels by incorporating into each of them individually an essential oil, namely lemongrass and cloves, and subsequently evaluating the antimicrobial activity by minimum inhibitory concentration (MIC) testing. The oils and gels were tested in parallel and resulted in a similar profile that can be observed in the inhibition concentration. This was a preliminary study that merits further investigation, which may progress to stability testing and evaluation of lower concentrations incorporated into the gel base.